A Semiempirical Method to Estimate Actual Evapotranspiration in Mediterranean Environments. (29th November 2018) - Chiesi, Marta; Battista, Piero; Fibbi, Luca; Gardin, Lorenzo; Pieri, Maurizio; Rapi, Bernardo; Romani, Maurizio; Maselli, Fabio
Abstract : Actual evapotranspiration (ETA ) is a major term of site water balance whose knowledge is essential for numerous purposes. The classical ETA estimation approach based on the use of multitemporal crop coefficients (Kc) cannot be applied in water-limited environments without proper correction. Such correction can be theoretically obtained by means of soil water content (SWC) measurements, which, however, are affected by several drawbacks, due to both their technical and operational characteristics. The current paper proposes a method to normalize annual SWC datasets and integrate them in an ETA estimation procedure suitable for monitoring both agricultural and natural Mediterranean ecosystems. Differently from previous approaches, the SWC normalization is obtained using data-specific information, which renders the new method mostly insensitive to the mentioned problems. The method is first described and then applied in three case studies representative of different Mediterranean ecosystems (i.e., grassland, coniferous, and deciduous forests). The results are evaluated versus latent heat measurements taken by eddy covariance flux towers. Satisfactory accuracy is obtained in all three case studies, with advantages and limitations which are discussed in the final concluding sections.